Conciliation ou agression : Un examen de quelques facteurs susceptibles d’influencer la politique étrangère soviétique au cours des années 80. - Marantz, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
This paper analyzes the way in which internal forces are likely to affect Soviet foreign policy over the next few years. Four developments are examined: potential Soviet petroleum shortages, the growing Soviet Muslim population, the slowdown in the rate of economic growth in the Soviet Union, and the imminent post-Brezhnev succession struggle. The question is posed: Will these factors soon impel the Soviet Union toward foreign expansion and adventurism?It is our conclusion that two of these factors, the leveling off of oil production and the rapid growth of Soviet Muslims, are not likely to have a strong influence on Soviet foreign policy. On the other hand, the decline in growth rates and the demise of Brezhnev are likely to have a major impact on future Soviet policies. The Soviet system is not experiencing a terminal crisis, but it is definitely laboring under growing burdens. It would be a mistake, however, to assume that this will necessarily result in foreign expansion. A new, rejuvenated leadership may well seek a relaxation of tensions, as it did upon Stalin’s death in 1953, so as to create favorable conditions for dealing with its pressing problems. The future remains highly uncertain. International developments will be at least as important as domestic factors, and much will depend upon the policies adopted by Western governments.